#TITLE_ALTERNATIVE# - ZAKIAH DRAJAT (NIM 10107026); Pembimbing : Prof. Dr. Edy Soewono, RIZKA
In the design process of nuclear reactor there are three analysis to be done i.e. analysis of neutronic, thermal hydraulic analysis and thermodynamic analysis. The focus in this …nal project is the thermal hydraulic analysis, which has a very important role in terms of system eÃ‚Â¢ ciency and the selection of the opti- mal design. This analysis is performed in a type of Gas Cooled Fast Reactor (GCFR) using cooling Helium (He). The heat from nuclear …ssion reactions in nuclear reactors will be distributed through the process of conduction in fuel elements. Furthermore, the heat is delivered through a process of heat convec- tion in the ‡uid ‡ow in cooling channel. Temperature changes that occur in the cooling channels cause a decrease in pressure at the top reactor core. The governing equations in each channel consist of mass balance, momentum bal- ance, energy balance, mass conservation and ideal gas equation. The problem is reduced to …nding ‡ow rates in each channel such that the pressure drops at the top of the reactor core are all equal. The problem is solved numerically with the genetic algorithm method. Flow rates and temperature distribution in each channel are obtained here.